2006
DOI: 10.1074/jbc.m508937200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Stability of Mitogen-activated Protein Kinase Kinase-2 mRNA and Phosphorylation of Poly(A)-binding Protein (PABP) in Cells Overexpressing PABP

Abstract: The poly(A)-binding protein (PABP) is an important regulator of mRNA translation and stability. The cellular level of PABP is controlled by regulating its mRNA translation by a feedback mechanism. The important aspect of this mechanism is that PABP binds to an adenosine-rich cis-element at the 5-untranslated region of its own mRNA and inhibits its translation. To assess the importance of controlling the PABP level, we studied the effect of PABP overexpression on the transcription profile using the microarray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Using wild-type and mutant L1 constructs, we demonstrated that excessive overexpression of both PABPs caused hypersensitivity to puromycin. This is consistent with previous studies which showed that the consequences of unregulated overexpression of PABPN1 and PABPC1 included an increased cell doubling time, a reduced cloning efficiency, and a significantly changed expression level for at least 202 different genes (12,14,47,49).…”
Section: Discussionsupporting
confidence: 81%
“…Using wild-type and mutant L1 constructs, we demonstrated that excessive overexpression of both PABPs caused hypersensitivity to puromycin. This is consistent with previous studies which showed that the consequences of unregulated overexpression of PABPN1 and PABPC1 included an increased cell doubling time, a reduced cloning efficiency, and a significantly changed expression level for at least 202 different genes (12,14,47,49).…”
Section: Discussionsupporting
confidence: 81%
“…Alterations in the cellular level of PABP do not only affect synthesis of a variety of proteins, but the cellular protein expression profile as well (Ma et al, 2006). Overexpression of PABP leads to defects in cell division of the fission yeast Saccharomyces pombe (Tallada et al, 2002) and increases the translation termination efficiency in Saccharomyces cerevisiae (Cosson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray profiling of cells aberrantly expressing RBPs has been employed to demarcate mRNA/RBP networks [25][26][27][28][29][30][31][32][33]. While this approach has been useful in identifying potential targets of tissue-specific RBPs [29,31], it has also revealed transcripts affected by proteins considered to be general processing factors.…”
Section: Genomic Approaches Define the Mrna Targets Of Rbpsmentioning
confidence: 99%